PENGEMBANGAN MODUL PEMBELAJARAN DIGITAL BERBASIS E-LEARNING PADA MATAKULIAH PERAKITAN KOMPUTER DI STKIP MUHAMMADIYAH MUARA BUNGO - fauziah fauziah; Nafsul Muthmainah (Jurnal Muara Pendidikan, 2021)
The very rapid development of science and technology in the Industrial Revolution Era 4.0 (ERI 4.0) also has an impact on the world of education, where the use of information technology is increasing in the world of education. The recent intense use of e-learning in the world of education has also been triggered by the COVID-19 pandemic which has resulted in the face-to-face learning process not being carried out directly, so the online learning process must be carried out. The online learning that was carried out experienced many obstacles, one of which was the absence of a learning module specifically designed for online learning. So it is necessary to develop an E-Learning-Based Learning Module. The purpose of this research is to produce learning modules that can be used in the learning process through E-Learning. This research is a research and development research and development (R&D). The development model used in this study is a 4-D model (Four D-Model), which consists of 4 main stages, namely, Define, Design, Develop and Disseminate. The research achievement is to produce a valid, practical, and effective E-Learning-Based Learning Module in Computer Assembly Course. This research will be conducted on second semester students of STKIP Muhammadiyah Muara Bungo. The sampling technique used is total sampling. The data analysis that will be used in this research is quantitative and qualitative descriptive analysis. From the results of this development study, it is hoped that the learning media for the E-Learning-Based Learning Module (Validity, Practicality, and Effectiveness) of the Computer Assembly course at STKIP Muhammadiyah Muara Bungo will be obtained.